Fetal Midgut Volvulus with a Cystic Appearance, Accompanying a Sinus Rhythm and an Increased Peak Systolic Velocity without Anemia - Metin Kaba; Aysegul Oksuzoglu; Gokcen Kaba; Hakan Timur; Eren Akbaba; Kadriye Turgut (Case Reports in Obstetrics and Gynecology)
A midgut volvulus rarely occurs in a fetus; however, when it does, it requires an immediate diagnosis and surgery. Thirty-week pregnant was referred to our clinic with a diagnosis of a fetal abdominal cystic mass and preterm labor. The initial ultrasound examination revealed a female fetus with a 55 × 50 mm cystic mass in the lower abdomen, which was preliminarily diagnosed as an ovarian cyst. There was a sinusoidal rhythm on cardiography. The middle cerebral artery peak systolic velocity was 60.4 cm/sec, compatible with 1.49 MoMs that suggested fetal anemia on Doppler examination. Uterine contractions were observed with tocography and maternal hydration was administered for tocolytic treatment. Despite hydration, uterine contractions continued and the infant was delivered. A newborn ultrasonographic evaluation revealed a 6 cm abdominal cyst, and plain abdominal radiographs revealed distended loops of the small bowel on the left side. Emergency surgery was performed. A midgut volvulus leading to dilatation and necrosis of the small bowel without anatomical causes was observed during laparotomy. The necrotic bowel loop was resected and an end-to-end anastomosis was performed. The newborn died due to multiorgan failure. Obstetricians should be familiar with the appropriate diagnosis and management of a fetal volvulus.